2018
DOI: 10.1007/s12237-018-0479-3
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Lighting at Night in Estuaries—Implications from Individuals to Ecosystems

Abstract: Artificial lighting at night (ALAN) produced by urban, industrial, and roadway lighting, as well as other sources, has dramatically increased in recent decades, especially in coastal environments that support dense human populations. Artificial Blightscapes^are characterized by distinct spatial, temporal, and spectral patterns that can alter natural patterns of light and dark with consequences across levels of biological organization. At the individual level, ALAN can elicit a suite of physiological and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 186 publications
(224 reference statements)
1
81
0
3
Order By: Relevance
“…The fourth is an under-examined side effect of constant light exposure on the onset of increased Daphnia reproduction under certain levels of salinity and/or acidity stress that are considered otherwise unfavourable for exponential reproduction. Light pollution effects, in terms of artificial light, sky glow and interference with daylight-night-time patterns, which increasingly affect aquatic ecosystems and ecological interactions [34,106], are becoming a serious concern associated with urbanisation and industrialised zones with increasing human population around the globe [30,34,107110]. The far-reaching effects of extended light exposure [34] may not only lead to changes in vital phototactic behaviours with disruptive impacts on the aquatic system [30,34], but may also extend to how zooplankton respond to a cocktail of stressors [77,111].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fourth is an under-examined side effect of constant light exposure on the onset of increased Daphnia reproduction under certain levels of salinity and/or acidity stress that are considered otherwise unfavourable for exponential reproduction. Light pollution effects, in terms of artificial light, sky glow and interference with daylight-night-time patterns, which increasingly affect aquatic ecosystems and ecological interactions [34,106], are becoming a serious concern associated with urbanisation and industrialised zones with increasing human population around the globe [30,34,107110]. The far-reaching effects of extended light exposure [34] may not only lead to changes in vital phototactic behaviours with disruptive impacts on the aquatic system [30,34], but may also extend to how zooplankton respond to a cocktail of stressors [77,111].…”
Section: Resultsmentioning
confidence: 99%
“…Meyer & Sullivan (2013) demonstrated that ecological light pollution through increased night lighting modifies community composition, structure, and characteristics and thus ecosystem functioning via alteration of nutrient exchange and aquatic–terrestrial fluxes of invertebrates [32]. These altered fluxes may have cascading effects through riparian and aquatic food webs [33,34]. However, although a number of studies endeavoured to shed light on the effects of darkness and light at night on the physiology, behaviour, growth and development, and fitness of a range of aquatic organisms [3436], the effect of lack of photoperiod, on daphnid phenotype, fitness and survival is surprisingly poorly studied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, light pollution can cause cascading eff ects in habitats, restructuring ecological communities by modifying the interactions between species and impacting pollination and seed dispersal . As well ALAN implications in estuaries from individuals to habitats (Zapata et al, 2019) as well as in stream and riparian habitats (Manfrin et al, 2018;Perkin et al, 2011) have been analised.…”
Section: Introductionmentioning
confidence: 99%